2002
DOI: 10.1074/jbc.m200981200
|View full text |Cite
|
Sign up to set email alerts
|

Galectins-3 and -7, but not Galectin-1, Play a Role in Re-epithelialization of Wounds

Abstract: Disorders of wound healing characterized by impaired or delayed re-epithelialization are a serious medical problem. These conditions affect many tissues, are painful, and are difficult to treat. In this study, using cornea as a model, we demonstrate for the first time the importance of carbohydrate-binding proteins galectins-3 and -7 in re-epithelialization of wounds. In two different models of corneal wound healing, re-epithelialization of wounds was significantly slower in galectin-3-deficient (gal3 ؊/؊ ) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
170
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 37 publications
9
170
0
1
Order By: Relevance
“…Alternatively, galectin-7 may be secreted through the posodomes, which would be consistent with the recent discovery that these structures are sites of secretion (Linder, 2007). In support of this hypothesis, Cao et al (2002) found that adding exogenous galectin-7 accelerates the rate of healing of wounded cornea. Once externalized, like other members of this gene family, galectin-7 might function as a matricellular molecule modulating adhesion, for example by regulating interactions between integrins and ECM components and/or by rapidly remodelling local ECM (Hikita et al, 2000;Levy et al, 2001;Elola et al, 2007).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Alternatively, galectin-7 may be secreted through the posodomes, which would be consistent with the recent discovery that these structures are sites of secretion (Linder, 2007). In support of this hypothesis, Cao et al (2002) found that adding exogenous galectin-7 accelerates the rate of healing of wounded cornea. Once externalized, like other members of this gene family, galectin-7 might function as a matricellular molecule modulating adhesion, for example by regulating interactions between integrins and ECM components and/or by rapidly remodelling local ECM (Hikita et al, 2000;Levy et al, 2001;Elola et al, 2007).…”
Section: Discussionsupporting
confidence: 72%
“…Several lines of evidence indirectly suggested that galectin-7 might play a role in epithelial tissue response to environmental stimuli. First, galectin-7 could intervene in the process of wound-healing because it is up-regulated in wounded cornea (Cao et al, 2003) and addition of the recombinant protein accelerates the speed of healing in culture (Cao et al, 2002). Second, galectin-7 has been described as a proapoptotic factor involved in the epidermal response after UVB injury.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased cell migration on GnT-IIILm332 was not induced by exogenous galectin-3, because modification of Lm332 by GnT-III reduced its ability to bind to galectin-3. These results strongly suggest that galectin-3 may be a cofactor for Lm332-induced cell motility during wound healing and squamous cell carcinoma tumor progression conditions that are associated with GnT-V overexpression (35,36). Therefore, the opposing galectin functions may be attributed to FIGURE 6.…”
Section: Discussionmentioning
confidence: 96%
“…Cytosolic galectin-3 is involved in the regulation of cell proliferation, differentiation, survival, and death (33). Galectin-3 is highly expressed in some cancers, including the human skin cancer squamous cell carcinoma (34,35), and at the leading edge of wound sites (36). Galectin-3 forms a lattice or cell surface microdomain, which links cytokine receptors on the cell surface (37).…”
mentioning
confidence: 99%
“…The findings that (i) galectin-3 expression, e.g., in placenta, 54 epithelium of the tongue 55 and keratinocytes, 56 correlates with C4.4A expression and that (ii) galectin-3 57 and C4.4A become upregulated during wound healing 48 point toward functional relevance of the C4.4A-galectin-3 association in supporting cell migration. Galectin-3 is found on the plasma membrane, in the cytosol and in the nucleus.…”
Section: C44a Associates With Galectin-3mentioning
confidence: 95%